Encountering the ‘Other’: Pilgrims, Tourists and Boatmen in the City of Varanasi - Doron, Assa (The Australian journal of anthropology, 2005)
Contemporary studies of tourism in the ‘Third World’ often focus on the farreaching economic, cultural and environmental consequences of tourism on local populations. Scholars have argued that guest/host interactions reflect a relation of domination in which, much like imperialism, wealthy Western tourists travel in search of the exotic Orient. The tourists are then served and catered to by local communities who are dependent on their business. Such polarities tend to privilege the ‘guests’ as the purveyors of change, while the creative and innovative practices of the host group are rendered invisible. In this paper, I examine the boatmen of Varanasi and their role as culture brokers, negotiating the sacred city for visitors who include pilgrims, domestic and foreign tourists. Concentrating mostly on the relationship between the boatmen and foreign tourists, I look at the multiple strategies and tactics that boatmen have developed to satisfy their needs and desires to their own advantage. Such techniques vary according to the visitors and their desired experience. Thus, the boatmen are quick to ‘tune in’ to those with whom they are dealing. Moreover, the close encounters that boatmen have with tourists enable them to view Western culture as well as their own local culture critically.